2013
DOI: 10.1007/s40519-013-0057-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of individuals who report present and past weight loss behaviours: results from a Canadian university community

Abstract: Purpose To characterise individuals who reported present and past weight loss behaviours on psycho-behavioural factors known to influence body weight, e.g. overeating, dietary restriction. Methods An online questionnaire was distributed to a university community. Questions pertaining to present weight loss, previous weight loss, eating behaviour tendencies, perceived stress and sleep quality were answered by 3,069 individuals. Body weight and height were selfreported. Results Present and past weight loss behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In men only, those sleeping ≤6 h a night had attempted dieting and had had IWL more often than those sleeping 7 to 8 h a night. In accordance, a Canadian study showed a short sleep duration to be associated with dieting attempts and previous weight loss [72]. A short sleep duration has also been linked to obesity and findings even suggest that it acts as an obstacle to weight loss [73].…”
Section: Discussionmentioning
confidence: 85%
“…In men only, those sleeping ≤6 h a night had attempted dieting and had had IWL more often than those sleeping 7 to 8 h a night. In accordance, a Canadian study showed a short sleep duration to be associated with dieting attempts and previous weight loss [72]. A short sleep duration has also been linked to obesity and findings even suggest that it acts as an obstacle to weight loss [73].…”
Section: Discussionmentioning
confidence: 85%
“…In addition to facilitating disordered eating and eating disorders, dieting has been found to have negative impacts on mental and physical health (e.g. Bacon and Aphramor, 2011; Gallant et al, 2013; McFarlane et al, 1999; Tomiyama et al, 2010) and has proven to be ineffective for long term weight loss and even leading to weight gain (Neumark-Sztainer et al, 2012; Pietilainen et al, 2012; Stice et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…compared to those who didn’t report unhealthy weight loss behaviours [ 9 ]. Another adverse consequence of unhealthy weight loss strategies include the potential development of eating disorders, which has important implications for health later in life [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%